HCV‐infected cells and differentiation increase monocyte immunoregulatory galectin‐9 production. Issue 3 (16th October 2015) - Harwood, Noah M. K.; Golden‐Mason, Lucy; Cheng, Linling; Rosen, Hugo R.; Mengshol, John A.
Abstract : HCV subject monocytes‐derived macrophages increased gal‐9, with the highest levels of non‐classical monocytes. Abstract : The lectin galectin‐9 may help establish and maintain chronic hepatitis C virus infection. Galectin‐9 is elevated in the liver and sera of hepatitis C virus patients, induces apoptosis of hepatitis C virus‐specific T cells, and increases inhibitory regulatory T cells. Kupffer cells stain strongly for galectin‐9 protein in hepatitis C virus patients. In the current study, we determined stimuli that induce galectin‐9 production by monocytes and macrophages in hepatitis C virus infection. With the use of real‐time PCR and flow cytometry, we analyzed galectin‐9 mRNA and protein from human monocytes cocultured with hepatitis C virus‐infected cells or noninfectious hepatitis C virus subgenomic replicon cells. We focused on finding the stimuli for galectin‐9 production. Additionally, we measured galectin‐9 during monocyte‐to‐macrophage maturation. Finally, we examined galectin‐9 in peripheral monocytes from hepatitis C virus patients using flow cytometry. Galectin‐9 mRNA increased 8‐fold when primary monocytes were exposed to hepatitis C virus‐‐infected cells. Maximum induction required proximity or contact and did not require IFN‐γ or hepatitis C virus virions. Coculture of monocytes with subgenomic replicon cells increased galectin‐9 5‐fold, and purified exosomes from infected cells stimulated galectin‐9 production. Stimulation of monocyte TLR3, ‐7, and ‐8 increased galectin‐9 production. Differentiation of monocytes to macrophages increased galectin‐9, and nonclassic monocytes from hepatitis C virus patients had the highest levels of galectin‐9. Hepatitis C virus‐infected cells stimulated monocytes to produce galectin‐9 in close proximity, possibly, in part, as a result of exosomes and endosomal TLRs. Differentiation of monocytes to macrophages increased galectin‐9. Nonclassic monocytes from hepatitis C virus patients express the highest galectin‐9 levels, suggesting they may contribute to elevated galectin‐9 and adaptive immune inhibition in hepatitis C virus infection.